The complete guide to roofing & siding : choose, install & maintain roofing & siding materials (Complete guide, 2013)
"This updated 3rd edition of Black & Decker's Complete Guide to Roofing & Siding provides detailed and updated information on modern materials and techniques for evaluating, installing, and maintaining a wide variety of roofing and siding materials"--Provided by publisher.